Mass Spectrum and Decay Constants of Heavy Quarkonia: Mass Spectrum and Decay Constants of Heavy Quarkonia - Ahmad, Tasawer Shahzad; Hussain, Talab; Sultan, M. Atif (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this paper, a non-relativistic potential model is used to find the solution of radial Schrodinger wave equation by using Crank Nicolson discretization for heavy quarkonia ( ̅, ̅). After solving the Schrodinger radial wave equation, the mass spectrum and hyperfine splitting of heavy quarkonia are calculated with and without relativistic corrections. The root means square radii and decay constants for S and P states of c ̅ and ̅ mesons by using the realistic and simple harmonic oscillator wave functions. The calculated results of mass, hyperfine splitting, root means square radii and decay constants agreed with experimental and theoretically calculated results in the literature.